FAKTOR PENGUNGKIT DAN STRATEGI PENINGKATAN PENGELOLAAN LINGKUNGAN OLEH PERKEBUNAN DAN PABRIK KELAPA SAWIT DI KABUPATEN BATANG HARI - novia susianti; Sukmal Fahri; Abdul Salam Lubis (Pusbindiklat - LIPI, 2020)
Environmental management by the oil palm plantation industry has become a necessity in minimizing negative impacts on the environment that have emerged from the construction to the operation stage. The government has made a preventive effort by requiring every industry performer to manage the environment by following the ownership of the company's environmental documents. However, in reality, there are still companies that have not implemented this effort, including in Batang Hari Regency as the regency with the highest number of oil palm companies in Jambi Province. This study aims to identify the lever factors and environmental management strategies by oil palm industry players in Batang Hari District. Data collection was carried out through in-depth interviews with the government, companies and village communities in the study areas, document review, observation, and focus discussion group (FGD) to the district, sub-district and village government research sites. The determination of priority levers is done by determining the important levers first with an average criterion of ≥75%, followed by fit/gap analysis by mapping important factors in quadrant I, and strategies to improve environmental management efforts are carried out using a prospective promethee analysis. The results showed that there were three priority lever factors and six factors that were advantages to improve environmental management. The strategy through the Walfare Pluralism (WP) approach is the best approach with the support of the contribution of the nine factors. This approach emphasizes the role of government, companies and communities through the principle of a five-sector approach (public sector, private sector, voluntary sector, mutual aid, and informal sector) in improving environmental management.